Pelatihan Pengenalan Budaya Kerja melalui Program Magang I di SDN 010 Langgini - Nurhaswinda, Nurhaswinda; Rizal, Muhammad Syahrul; Husna, Asmaul; Masitoh, Cahya; Lestari, Etika; Nugraheni, Nonik; Putri, Nurpita; Zahra, Lativa; Khairunnisa, Khairunnisa; Marsela, Ranti; Putri, Nabila; Selviani, Seri (Universitas Pahlawan Tuanku Tambusai, 2025)
The internship program is part of a compulsory curriculum that aims to provide direct experience to students in the world of education. This article aims to describe the implementation of the Internship I program carried out by fourth semester students of the PGSD Study Program at Pahlawan Tuanku Tambusai University at SDN 010 Langgini. This activity is carried out through observation, interviews, and direct involvement in the learning process and school activities. The results of this internship activity show an increase in students' understanding of school management, the learning process, and instilling student character values. This program not only improves students' pedagogical and social competencies, but also contributes to school activities. Thus, Internship I becomes a forum for community service as well as strengthening the competence of prospective teachers.